2020
DOI: 10.1038/s41598-020-73254-2
|View full text |Cite
|
Sign up to set email alerts
|

Picosecond multilevel resistive switching in tantalum oxide thin films

Abstract: The increasing demand for high-density data storage leads to an increasing interest in novel memory concepts with high scalability and the opportunity of storing multiple bits in one cell. A promising candidate is the redox-based resistive switch repositing the information in form of different resistance states. For reliable programming, the underlying physical parameters need to be understood. We reveal that the programmable resistance states are linked to internal series resistances and the fundamental nonli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 51 publications
2
49
0
Order By: Relevance
“…Noticeably, the onset of the SET probability curve shifts to lower voltages when increasing the pulse duration. This phenomenon has been studied before and reflects the typical SET switching kinetics (Fleck et al, 2016;Witzleben et al, 2017;Nishi et al, 2018;Cüppers et al, 2019;Bengel et al, 2020;Böttger et al, 2020). However, the voltage range, where the probability is neither 0 nor 100%, remains roughly constant at around 160 mV, with some deviations caused by the limited number of tries.…”
Section: Cycle-to-cycle Switching Stochasticity Over Multiple Orders Of Magnitude In Switching Timesupporting
confidence: 54%
“…Noticeably, the onset of the SET probability curve shifts to lower voltages when increasing the pulse duration. This phenomenon has been studied before and reflects the typical SET switching kinetics (Fleck et al, 2016;Witzleben et al, 2017;Nishi et al, 2018;Cüppers et al, 2019;Bengel et al, 2020;Böttger et al, 2020). However, the voltage range, where the probability is neither 0 nor 100%, remains roughly constant at around 160 mV, with some deviations caused by the limited number of tries.…”
Section: Cycle-to-cycle Switching Stochasticity Over Multiple Orders Of Magnitude In Switching Timesupporting
confidence: 54%
“…In consequence, overcoming this dilemma requires a strong non-linear dependence of the switching time on the applied voltage. In our recent publication, we have shown that the SET time of VCM devices depends indeed strongly non-linearly on the applied voltage in the range from 250 ps to 10 4 s [5], which is sufficient to address the voltagetime-dilemma.…”
Section: Introductionmentioning
confidence: 94%
“…To predict the power consumption of our memristive circuit approach in realistic applications in IoT devices, we replaced the original transistor model in Verilog-A with a model corresponding to the 22-nm silicon-on-insulator (SOI) process with a channel length of ∼20 nm, close to the state-of-the-art. The switching speed of the memristor was also adapted to 10 ps, according to indications of switching dynamics found in similar devices [18]. The test circuit consists of a fan-out-of-4 (FO4) memristive inverters.…”
Section: Memristive Circuits For Iot Devicesmentioning
confidence: 99%